Mycorrhizal functioning as part of the survival mechanisms of barley (Hordeum vulgare L) at long-term heavy metal stress - Biró, Borbála (Acta Biologica Szegediensis, 2005)
Pot experiment was design to study the inside and outside root colonization of arbuscular mycorrhizal fungi (AMF) on the barley (Hordeum vulgare L) at various types and loadings of several heavy metals or toxic elements. Soils of the pots were originating from a long-term field experiment, where 13 metal salts, such as the Al, As, Ba, Cd, Cr, Cu, Hg, Mo, Ni, Pb, Se, Sr, Zn was applied in 4 gradients (0, 30, 90, 270 mg.kg-1 dry soil), 12 years prior the study. Beside the relative and absolute frequency (F%, M%), the arbusculum richness (a%, A%) and the sporulation intensity (g-1 dry soil) of the AM fungi the biomass production and the element accumulation of the barley was also measured. The inside mycorrhizal colonization of the roots proved to be much less sensitive to the long-term heavy metal stress. Except the increased mycorrhizal sporulation at Ni (36 g-1 soil), several toxic elements, such as the Al, As, Ba, Cr, Cu, Pb, Se, Sr and Zn could reduce the spore-numbers of the AM fungi significantly. This lower density, however was not affecting to the biomass production of the barley. At some metals with lower AMF sporulation an increased root (and fungal) biomass were found at the As, Ba, Cr, Cu and Cd elements. Increased arbusculum richness (A%) could be developed, on the other hand at the Hg and Pb metals. Such various mechanisms of the mycorrhizal functioning can offer a general aid for the host-plants to cope with the environmental stress, which could result a more balanced shoot (and yield) biomass production.